Empowered collective: Formulating a black feminist information community model through archival analysis. Issue 1 (22nd October 2020) - Gray, LaVerne
Abstract: This poster presents a critical‐qualitative evidence inquiry approach to examine the information dynamics of African American mothers in an historic (1955–1970) Chicago public housing community. This research builds upon initial interest in their activism for the construction of a neighborhood library, to exploring the information rich system emanating from the community they inhabit (Gray In a collective voice: Uncovering the black feminist information community of activist‐mothers in Chicago Public Housing, 1955‐1970). The three phase eight step qualitative evidence approach includes descriptive and complex theoretical analysis contributing to the formulation of a Black Feminist Information Community (BFIC) model.